The Influence of Imagery on The Improvement of Three Point Shoot Ability in Basketball Games - Pamungkas, Yogha Tri (Department of Physical Education, Sport, Health and Recreation, 2018)
The purpose of this study was to determine the effect of imagery on improving the three point shoot ability. The population of this study are extracurricular participants of men’s basketball SMK Negeri 1 Gombong with twenty number of students and the sampling technique used is total sampling. The research method using True Experimental method, that is Pretest-Posttest Control Group Design. The control and experimental group was divided by matched by subject (M-S) method. The data analysis used are normality test, homogeneity test and hypothesis test. The results showed that the exercise of imagery has a significant effect on the improvement of basketball three point shoot skills. The average of pretest is 14,3 and the average of posttest is 17,7, therefore the influence of imagery to improve three point shoot ability is 19,5%. The conclusion of this research that there is significant influence from imagery exercise to increase basketball three point shoot ability of SMK Negeri 1 Gombong’s extracurricular participants.